2005
DOI: 10.1155/mi.2005.256
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Cytokine Levels in Active Tuberculosis With Treatment

Abstract: It has been reported that IFN-γ, TNF-α, and IL-12 stimulate, and that IL-10, TGF-β, and IL-4 suppress the protective immune response against tuberculosis. We aim to evaluate changes in the serum levels of pro and antiinflammatory cytokines in active pulmonary tuberculosis (APTB) and the possible effects of treatment on these changes. Serum IL-12p40, IL-4, IL-10, TNF-α, IFN-γ, and TGF-β1 levels were determined in 20 APTB cases (group 1) before and 2, 4, and 6 months after therapy. The same parameters were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
56
5
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 40 publications
10
56
5
2
Order By: Relevance
“…These results are in agreement with those of other studies. (24,26) In one study mentioned previously, (14) the cytokine levels were found to be equivalent to those of the control group at the end of therapy. Again, the divergences in the results are likely related to the differences in the methodology used by the authors, the clinical status of the patients studied, the period of evolution of the disease or treatment and other factors.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…These results are in agreement with those of other studies. (24,26) In one study mentioned previously, (14) the cytokine levels were found to be equivalent to those of the control group at the end of therapy. Again, the divergences in the results are likely related to the differences in the methodology used by the authors, the clinical status of the patients studied, the period of evolution of the disease or treatment and other factors.…”
Section: Discussionmentioning
confidence: 80%
“…There is evidence to suggest that TNF-α is necessary at the beginning of the inflammatory process in order to limit the multiplication of mycobacteria. (18,19,26) Other studies demonstrated that high TNF-α initial levels in PTB decreased significantly during the treatment, while the inflammatory process decreased at the same time. (14,26) In the present study, TNF-α production by monocytes, stimulated or not, was also lower in the controls than in the patients before treatment, after three months of treatment and at the end of treatment.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This issue may be addressed in the present study by the presence of lower albumin (natural antioxidant) in those with active pulmonary tuberculosis. Proinflammatory cytokines like IL-6, IL-1, TNF-α and IFN's which are known to down regulate serum lipid levels by interfering withlipid metabolism (Vanet.al 1994;Henrich 1990) have also been shown to increase during the onset of active tuberculosis (FigenDeveci et al, 2005).…”
Section: Resultsmentioning
confidence: 99%